Black. Queer. Southern. Women. : An Oral History - Johnson, E. Patrick, 1967- (Book collections on Project MUSE., 2018)
"Drawn from the life narratives of more than seventy African American queer women who were born, raised, and continue to reside in the American South, this book powerfully reveals the way these women experience and express racial, sexual, gender, and class identities--all linked by a place where such identities have generally placed them on the margins of society. Using methods of oral history and performance ethnography, E. Patrick Johnson's work vividly enriches the historical record of racialized sexual minorities in the South and brings to light the realities of the region's thriving black lesbian communities. At once transcendent and grounded in place and time, these narratives raise important questions about queer identity formation, community building, and power relations as they are negotiated within the context of southern history. Johnson uses individual stories to reveal the embedded political and cultural ideologies of the self but also of the listener and society as a whole. These breathtakingly rich life histories show afresh how black female sexuality is and always has been an integral part of the patchwork quilt that is southern culture."--